Characterization of Wet Powder‐Sprayed Zirconia/Calcium Phosphate Coating for Dental Implants. (9th April 2013) - Pardun, Karoline; Treccani, Laura; Volkmann, Eike; Li Destri, Giovanni; Marletta, Giovanni; Streckbein, Philipp; Heiss, Christian; Rezwan, Kurosch
Abstract Purpose Yttria‐stabilized zirconia (TZ) is used for dental applications because of its low toxicity and beneficial mechanical properties, but it does not stimulate bone regeneration around the implant due to its bioinertness. Therefore, hydroxyapatite (HA) coatings are often utilized to increase the surface bioactivity and to achieve a better osseointegration. These coatings, however, are chemically nonstable and provide a weak bonding to the substrate surface. Materials and Methods In this study, zirconia substrates were coated with a calcium phosphate/zirconia mixture to achieve ceramic coatings with a high bioactivity potential and a good mechanical stability. The coatings were obtained by wet powder spraying (WPS). Pure HA and TZ coatings were employed as reference materials. The coatings were characterized with regard to microstructure, surface roughness, and phase composition. Scratch tests were carried out to investigate the coating adhesion. The influence of the coating on the mechanical strength was evaluated with the ball on three balls test (B3B). In addition, zirconia dental implant screws were also coated and inserted in a biomechanical test block and bovine rip bone. Results After sintering, the mixed coating exhibited a porous morphology with a surface roughness of about 4 μm and a total porosity of 17%. Phase analysis showed a transformation from TZ and HA to calcium zirconium oxide and tricalcium phosphate. Investigations of the bond strength confirmed a strong adhesion of the mixed coating to the substrate, while the biaxial fracture strength was only slightly affected. Insertion experiments confirmed the scratch test results and evidenced an intact mixed coating on the zirconia screw. Conclusions The present study revealed a higher stability and firm adhesion of the mixed coating compared with a pure calcium phosphate coating. We also successfully demonstrate the particular versatility of the WPS technique for dental implants by coating a complex curved surface.